(Invited) Divide Et Impera: Towards New Frontiers with Atomic Layer Etching. (10th September 2015) - Lill, Thorsten; Kanarik, Keren J.; Tan, Samantha S.H.; Shen, Meihua; Pan, Yang; Marks, Jeffrey; Vahedi, Vahid; Gottscho, Richard A.
Abstract : Atomic layer etching (ALE) is emerging as a solution for advanced etch applications which require atomic scale fidelity /1/. In analogy to Atomic Layer Deposition (ALD), ALE is separated into two individual steps, one for surface modification and one for removal /2, 3, 4/. Similar to Reactive Ion Etching (RIE), the fundamental mechanism of ALE is based on ion-neutral synergism. Because of the time separation of the surface modification by neutrals and the removal step by ions, this synergism manifests itself in the saturation of the removal step. The modification step is saturated which means that the fundamental etch mechanism of directional ALE is chemically enhanced sputtering /5-8/. The window for directional ALE is given by the sputter threshold of the bulk material on the high end and the sputter threshold of the modified layer on the low end.